“Reflection” Penciptaan Komposisi Dengan Menerapkan Rumus Matematis Refleksi - Adi Wijaya (SELONDING, 2017)
The process of making works of art is a creative process that can be achieved in various ways, contemporary musical development today inevitably requires academics and practitioners to understand theories that support the process of making artwork, not only in terms of aesthetics and relationships to the environment but the in-depth responsibilities reviewed technical to the work itself. Technical mastery in the cultivation of good works can help and facilitate both the process and logical delivery to the general public and certainly can be understood so that messages brought the work to the public. Music is an objective phenomenon, one form of objectivity in the work of music is a correlation with mathematics that has the potential to be the source of creation. Keywords: Creation of composition, mathematical reflection